1995
DOI: 10.1128/aac.39.12.2610
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of synergy with fluconazole and either ibuprofen, sodium salicylate, or propylparaben against Candida albicans in vitro

Abstract: The combination of fluconazole with either ibuprofen, sodium salicylate, or propylparaben resulted in synergistic activity (fractional inhibitory index, <0.5) against Candida albicans NCYC 610 in a microdilution checkerboard assay. Synergism between miconazole and ibuprofen was also demonstrated. In three of four clinical isolates of C. albicans from AIDS patients, the combination of fluconazole and ibuprofen was synergistic. Preparation of the inoculum and the growth conditions used were those recommended by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 11 publications
4
45
0
Order By: Relevance
“…In the current investigation, combining ibuprofen with either nikkomycin Z or econazole produced an antifungal effect which was significantly greater than that obtained with each compound on its own (i.e., it resulted in synergism), while combining it with amphotericin B resulted in additivity. These results support observations by Scott et al (13), who reported synergistic interactions between ibuprofen and the azoles miconazole and fluconazole against C. albicans NCYC 610 by the checkerboard titration method. Combining ibuprofen with an antifungal drug may not only result in increased antifungal efficacy, but the recognized anti-inflammatory properties of ibuprofen could also prove to be clinically useful in the topical treatment of candidiasis and other fungal The results presented here indicate that the DAA is a useful method for initial assessments of the interactions between antifungal compounds, since it provides a more complete description of the interactions detected.…”
Section: Discussionsupporting
confidence: 82%
“…In the current investigation, combining ibuprofen with either nikkomycin Z or econazole produced an antifungal effect which was significantly greater than that obtained with each compound on its own (i.e., it resulted in synergism), while combining it with amphotericin B resulted in additivity. These results support observations by Scott et al (13), who reported synergistic interactions between ibuprofen and the azoles miconazole and fluconazole against C. albicans NCYC 610 by the checkerboard titration method. Combining ibuprofen with an antifungal drug may not only result in increased antifungal efficacy, but the recognized anti-inflammatory properties of ibuprofen could also prove to be clinically useful in the topical treatment of candidiasis and other fungal The results presented here indicate that the DAA is a useful method for initial assessments of the interactions between antifungal compounds, since it provides a more complete description of the interactions detected.…”
Section: Discussionsupporting
confidence: 82%
“…The increase of antifungal resistance increase the need for new antifungals. Many studies showed that NSAID showed activity against Candida [37,38,39] that led us to undergo this study on the activity of three non-steroidal antiinflammatory drugs on C. albicans and 2 non-albicans strains…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this is because echinocandins are typically fungicidal and have potent activity against most Candida species when administered alone. Other agents with limited antifungal activity on their own, including metronidazole (52), fluvastatin and pravastatin (41,136), nonsteroidal antiinflammatory agents (155,188,224), and quinolones (135), have been studied in combination with amphotericin B or triazoles, with a suggestion of positive effects occurring in all cases. The results of a recent report also suggested that when combined with fluconazole, terbinafine, or caspofungin, combinations of calcineurin inhibitors such as cyclosporine A and tacrolimus are highly synergistic for fungicidal effects (142).…”
Section: (D) Other Combinationsmentioning
confidence: 99%